Performance Analysis of Routing Algorithms in 2D Mesh Based NoC Under Varying Load Using Support Vector Machine - Syal, Nidhi; Sehgal, Vivek Kumar (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The paper presents the performance analysis of routing techniques on 3x3 mesh NOC topology. The effect of load variation in delay and total network energy for different types of routing is observed. The simulation is performed on the NOXIM network on chip simulator under random traffic conditions. The research involves developing of the classification model based on support vector machine for the performance analysis of both deterministic and adaptive routing schemes. The quality parameters provided as input to the model against the performance of routing algorithms based on Network-onChip platform are minimum delay, minimum energy and maximum throughput.